Validation of TICS for detection of dementia and mild cognitive impairment among individuals characterized by low levels of education or illiteracy: a population-based study in rural Greece. (11th November 2017) - Georgakis, Marios K.; Papadopoulos, Fotios C.; Beratis, Ion; Michelakos, Theodoros; Kanavidis, Prodromos; Dafermos, Vasilios; Tousoulis, Dimitrios; Papageorgiou, Sokratis G.; Petridou, Eleni Th.
Abstract: Objective: The efficacy of the most widely used tests for dementia screening is limited in populations characterized by low levels of education. This study aimed to validate the face-to-face administered Telephone Interview for Cognitive Status (TICS) for detection of dementia and mild cognitive impairment (MCI) in a population-based sample of community dwelling individuals characterized by low levels of education or illiteracy in rural Greece.Methods: The translated Greek version of TICS was administered through face-to-face interview in 133 elderly residents of Velestino of low educational level (<12 years). We assessed its internal consistency and test–retest reliability, its correlation with sociodemographic parameters, and its discriminant ability for cognitive impairment and dementia, as defined by a brief neurological evaluation, including assessment of cognitive status and level of independence.Results: TICS was characterized by adequate internal consistency (Cronbach's α : .72) and very high test–retest reliability (intra-class correlation coefficient: .93); it was positively correlated with age and educational years. MCI and dementia were diagnosed in 18 and 10.5% of the population, respectively. Its discriminant ability for detection of dementia was high (Area under the curve, AUC: .85), with a sensitivity and specificity of 86 and 82%, respectively, at a cut-off point of 24/25. TICS did not perform well in differentiating MCI from cognitively normal individuals though (AUC: .67).Conclusion: The directly administered TICS questionnaire provides an easily applicable and brief option for detection of dementia in populations of low educational level and might be useful in the context of both clinical and research purposes.